Psychological Maladjustment Mediates the Relation Between Remembrances of Parental Rejection in Childhood and Adults' Fear of Intimacy: A Multicultural Study. (December 2019) - Rohner, Ronald P.; Filus, Ania; Melendez-Rhodes, Tatiana; Kuyumcu, Behire; Machado, Francisco; Roszak, Joanna; Hussain, Sadiq; Chyung, Yun-Joo; Senese, Vincenzo P.; Daneshmandi, Saeede; Ashdown, Brien K.; Giovazolias, Theodoros; et al.
This study assesses interpersonal acceptance-rejection theory's (IPARTheory's) prediction that adults' (both men's and women's) remembrances of parental (both maternal and paternal) rejection in childhood are likely to be associated with adults' fear of intimacy, as mediated by adults' psychological maladjustment and relationship anxiety. The study also assesses the prediction that these associations will not vary significantly by gender, ethnicity, language, culture, or other such defining conditions. To test these predictions a sample of 3, 483 young adults in 13 nations responded to the mother and father versions of the Adult Parental Acceptance-Rejection Questionnaire (short forms), Adult Personality Assessment Questionnaire (short form), the Interpersonal Relationship Anxiety Questionnaire, the Fear of Intimacy Scale, and the Revised Personal Information Form. Results of multigroup analyses showed that adults' remembrances of both maternal and paternal rejection in childhood independently predicted men's and women's fear of intimacy in all 13 countries. However, remembered maternal rejection was a significantly stronger predictor of adults' fear of intimacy than was remembered paternal rejection. Results also confirmed the prediction in all 13 countries and across both genders that both maternal and paternal rejection independently predicted adults' psychological maladjustment and relationship anxiety, which in turn predicted fear of intimacy. In addition, psychological maladjustment partially mediated the relation between remembrances of maternal and paternal rejection, and adults' fear of intimacy in all 13 countries and both genders.